Золотой песок: роман / Полина Дашкова - Дашкова Полина (Полина Дашкова - лучшая среди лучших, 2020)
Экземпляры: ф.7 (20210205) / Инвентарный номер: 45544 / Цена: 490.00 / Авт.знак: Д 21 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44